Discourse Analysis of Prophetic Oracles: Woe, Indictment, and Hope - Hoyt, JoAnna M. (Hebrew studies, 2019)
Discourse analysis of the emic structures of Biblical Hebrew is an underdeveloped area of Hebrew linguistics. This lack of a linguistic examination has resulted in Hebrew scholars relying upon form criticism, which, though helpful, is lacking in objectivity and precision. This paper offers a discourse analysis of three prophetic oracle types: woe, indictment, and hope. Through a modified approach to Longacre's etic discourse structures, this paper examines the oracles' emic structures within Amos and Micah. Not only does this analysis provide a more objective process and more precise criteria for identifying genres than form criticism, but it also reveals otherwise overlooked discourse features such as skewing and peak marking elements, which are all necessary to more fully understand the intended purpose and function of the oracles.